Gestión de usuarios en la biblioteca de la Espam MFL - Sánchez Macías, Cinthia Mabel (2016)
The objective of the study was to implement a biometric module for user in the library of the ESPAM MFL, to expedite the identification in the Integrated Library Management System (ILMS) Koha, which is open source. The manual registration of users causes difficulties from collection to treatment, this is the proposal of Koha with biometric ID (product). It worked with the scrum development methodology, which allowed list requirements, sort them by priority and transform them into a pile of sprints, with the tasks and estimated time for completion. Besides, it used five activities, requirements, analysis, design, development and delivery; three roles were involved: the product owner, scrum master and team. The system was developed in the Framework. NET, with the development environment Visual Studio 2012, SQL Server 2012 database, and C# as the programming language; DigitalPersona U5000 for fingerprint reading were also used. After the respective tests, it is concluded that the application improves the identification of the Koha time, and this combination greatly reduces the time of user registration with the services, including the benefits of information management and security, ensuring the identity of the user.